An Attempt of Early Detection of Poor Outcome after Whiplash - Laporte, Sebastien; Wang, Danping; Lecompte, Jennyfer; Blancho, Sophie; Sandoz, Baptiste; Feydy, Antoine; Lindberg, Pavel; Adrian, Julien; Chiarovano, Elodie; de Waele, Catherine; Vidal, Pierre-Paul (Frontiers in Neurology, 2016)
The main concern with whiplash is that a large proportion of whiplash patients experience disabling symptoms or whiplash associated disorders (WAD) for months if not years following the accident. Therefore, identifying early prognostic factors of WAD development is important as WAD have widespread clinical and economic consequences. In order to tackle that question, our study was specifically aimed at combining several methods of investigation in the same WAD patients at the acute stage and six months later. Our longitudinal, open, prospective, multi-center study included 38 whiplash patients, and 13 healthy volunteers matched for age, gender, and socio-economic status with the whiplash group. Whiplash patients were evaluated 15 to 21 days after road accident, and 6 months later. At each appointment, patients underwent a neuropsychological evaluation, a full clinical neurological examination, neurophysiological and postural tests, oto-neurological tests, cervical spine cord Magnetic Resonance Imaging (MRI) with tractography (DTI). At 6-month, whiplash patients were categorized into two subgroups based on the results of the Diagnostic and Statistical Manual of Mental Disorders as having either favourable or unfavourable progression (an unfavourable classification corresponding to the presence of Post-Concussion Symptom PCS) and we searched retrospectively for early prognostic factors of WAD predicting the passage to chronicity. We found that patients displaying high level of catastrophizing at the acute stage and /or post-traumatic stress disorder associated with either abnormalities in head or trunk kinematics, abnormal test of the otolithic function and at the Equitest or a combination of these syndromes, turned to chronicity. That is, the association of a neuropsychological disorder with a somatic one was sufficient to explain the passage to chronicity. This study suggests that low-grade whiplash patients should be submitted as early as possible after the trauma to neuropsychological and motor control tests in a specialized consultation. In addition, they should be evaluated by a neuro-otologist for a detailed examination of vestibular functions, which should include cVEMP (Vestibular Evoked Myogenic Potential). Then, if diagnosed at risk of WAD, these patients should be subjected to an intensive preventive rehabilitation program, including vestibular rehabilitation if required.